ICT Equipment Investment and Growth in Low- and Lower-Middle-Income Countries - Haacker, Markus (IMF Working Papers; Working Paper, 2010)
While production of ICT equipment plays a subordinate role for economic growth in most of these countries, they do benefit from capital deepening arising from falling prices of ICT equipment. Adapting established growth accounting approaches to the data environment of low-income countries, we quantify the growth impacts of absorption of ICT equipment, finding that ICT-related capital deepening contributed 0.2 percentage points to growth in low-income countries, and 0.3 percentage points in low-middle-income countries. The latter is about half the level typically found for industrialized countries.